PEMANFAATAN TEKNIK CBIR BERBASIS CITRA WAJAH UNTUK OTOMASI SISTEM INFORMASI PEMBUATAN PASPOR - Zaidal, Nisar (IIB Darmajaya, 2012)
This research is done to build an application using CBIR Technique to detect if someone has made any passport or not. This application is useful to prevent passport forgery, an the further effect,this application also can prevent international crime. This application works with the facial image as a key image to match the image of a face that has been inserted into the database. The database contains facial images. This research show how algorithm works well in terms of precision and recall.With face image as the key to search face image that...